Himnas Kedei : a eulogy to the chair. - Alisauskiene, Janina; Kazakevicius, Ignas (Siauliai : Art gallery Laiptai, 2000)
Griskevicius, Algis ; Tuskenas, Balys ; Mikutis, Viktoras ; Kuzma, Saulius ; Sitonyte, Nijole ; Mykolaityte, Jurate ; Natalevicius, Liudvikas ; Simoliunai, Grazina ir Virginijus ; Katiliute, Audra ; Janulis, Vaidas et al.
litouws
kunstcatalogus
Keywords: Litouwen